Particular case of operator calculus for generalized functions with supports in cone - Solomko, A.V. (Carpathian Mathematical Publications, 2009)
In this work the construction of functional calculus for strongly continuous semigroups of operators in Schwartz distribution algebra on some cone is generalized. The partial case of vector valued calculus on the base of modification operator Fourier transformation is researched.